The Pulmonary Metastasectomy in Colorectal Cancer (PulMiCC) burden of care study: Analysis of local treatments for lung metastases and systemic chemotherapy in 220 patients in the PulMiCC cohort. (2nd August 2021) - Treasure, Tom; Farewell, Vern; Macbeth, Fergus; Batchelor, Tim; Milosevic, Misel; King, Juliet; Zheng, Yan; Leonard, Pauline; Williams, Norman R.; Brew‐Graves, Chris; Morris, Eva; Fallowfield, Lesley; et al.
Abstract: Aim: The aim of this work was to examine the burden of further treatments in patients with colorectal cancer following a decision about lung metastasectomy. Method: Five teams participating in the Pulmonary Metastasectomy in Colorectal Cancer (PulMiCC) study provided details on subsequent local treatments for lung metastases, including the use of chemotherapy. For patients in three groups (no metastasectomy, one metastasectomy or multiple local interventions), baseline factors and selection criteria for additional treatments were examined. Results: The five teams recruited 220 patients between October 2010 and January 2017. No lung metastasectomy was performed in 51 patients, 114 patients had one metastasectomy and 55 patients had multiple local interventions. Selection for initial metastasectomy was associated with nonelevated carcinoembryonic antigen, fewer metastases and no prior liver metastasectomy. These patients also had better Eastern Cooperative Oncology Group scores and lung function at baseline. Four sites provided information on chemotherapy in 139 patients: 79 (57%) had one to five courses of chemotherapy, to a total of 179 courses. The patterns of survival after one or multiple metastasectomy interventions showed evidence of guarantee‐time bias contributing to an impression of benefit over no metastasectomy. After repeated metastasectomy, a significantly higher risk of death was observed, with no apparent reduction in chemotherapy usage. Conclusion: Repeated metastasectomy is associated with a higher risk of death without reducing the use of chemotherapy. Continued monitoring without surgery might reassure patients with indolent disease or allow response assessment during systemic treatment. Overall, the carefully collected information from the PulMICC study provides no indication of an important survival benefit from metastasectomy.